In Vitro Assessment of Acaricidal and Reproductive Inhibitory Effects of Allium Sativum Clove Extracts against Rhipicephalus microplus - Dinkar Kale, Chandrakant; Kumar Jaiswal, Amit; Choudhury, Soumen; Sachan, Supriya; Agrawal, Vivek; Singh, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was carried out to investigate the in vitro efficacy of crude aqueous, ethanolic, and hydroethanolic extracts of Allium  sativum (garlic cloves) against Rhipicephalus microplus ticks, with a focus on their potential as novel botanical agents for tick control.  Bioassays were conducted on both fully engorged adult female ticks and larval stages using extract concentrations ranging from 6.25  mg/mL to 100 mg/mL. While adult and larval mortality was limited, a notable dose-dependent reduction in egg-laying capacity was  observed in treated female ticks compared to the untreated control group. This reproductive inhibition, revealed through the adult  immersion test (AIT), highlights a promising sublethal effect of A. sativum extracts. The larval packet test (LPT) yielded LC50 values of  88.43, 44.04, and 171.1 mg/mL for aqueous, ethanolic, and hydroethanolic extracts, respectively. Despite the modest direct acaricidal  activity, these findings underscore the potential of A. sativum to impair tick fecundity and contribute to integrated tick management  strategies. The observed interference with tick reproduction warrants further research into optimizing extract formulation and exploring  synergistic combinations for enhanced efficacy.
Keywords: Acaricidal AIT; Allium sativum; Crude extracts; LPT; Rhipicephalus microplus